Purity of graphene oxide determines its antibacterial activity. (13th May 2016) - Barbolina, I; Woods, C R; Lozano, N; Kostarelos, K; Novoselov, K S; Roberts, I S
Abstract: Nanomaterials based on two-dimensional (2D) atomic crystals are considered to be very promising for various life-science and medical applications, from drug delivery to tissue modification. One of the most suitable materials for these purposes is graphene oxide (GO), thanks to a well-developed methods of production and water solubility. At the same time, its biological effect is still debated. Here we demonstrate that highly purified and thoroughly washed GO neither inhibited nor stimulated the growth of E.coli, ATCC25922; E.coli NCIMB11943 and S.aureus ATCC25923 at concentrations of up to 1 mg ml −1 . Moreover, transmission electron microscopy (TEM) of GO exposed bacteria did not reveal any differences between GO exposed and not exposed populations. In contrast, a suspension of insufficiently purified GO behaved as an antibacterial material due to the presence of soluble acidic impurities, that could be removed by extended purification or neutralisation by alkaline substrates. A standardised protocol is proposed for the generation of clean GO, so it becomes suitable for biological experiments. Our findings emphasise the importance of GO purification status when dealing with biological systems as the true effect of material can be masked by the impact of impurities.